METODE KALIBRASI ONLINE UNTUK PEMANTAUAN KONDISI PERANGKAT INSTRUMENTASI REAKTOR NUKLIR BERBASIS ELECTRICAL SIGNATURE ANALYSIS - Bakhri, Syaiful (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2015)
Electrical signature analysis currently becomes an alternative in condition monitoring in nuclear power plants not only for stationary components such as sensors, measurement and instrumentation channels, and other components but also for dynamic componentssuch as electric motors, pumps, generator or actuators. In order to guarantee the accuracy, the calibration of monitoring systemis anecessary which practically is performed offline, under limited schedules and certain tight procedures. This research aims to introduce online calibration technique for electrical signature condition monitoring in order that the accuracy can be maintained continuously which in turn increases the reactor safety as a whole. The research was performed step by stepin detail from the conventional technique, online calibration using baseline information and online calibration using differential gain adjustment. Online calibration based on differential gain adjustment provides better results than other techniques even tough under extreme gain insertion as well as external disturbances such as supply voltages.